ATTENUATION OF SEISMIC WAVES IN METHANE GAS HYDRATE-BEARING SAND - Priest J.A.; Best A.I.; Clayton C.R.I. (My University, 2006)
Compressional wave (P wave) and shear wave (S wave) velocities (Vp and Vs, respectively) from remote seismic methods have been used to infer the distribution and volume of gas hydrate within marine sediments. Recent advances in seismic methods now allow compressional and shear wave attenuations (Qp-1 and Qs-1, respectively) to be measured. However, the interpretatio of these data is problematic due to our limited understanding of the effects of gas hydrate on physical properties. Therefore, a laboratory gas hydrate resonant column was developed to simulate pressure and temperature conditions suitable for methane gas hydrate formation in sand specimens and the subsequent measurement of both Qp-1 and Qs-1 at frequencies and strains relevant to marine seismic surveys. 13 dry (gas saturated) sand specimens were investigated with different amounts of methane gas hydrate evenly dispersed throughout each specimen. The results show that for these dry specimens both Qp-1 and Qs-1 are highly sensitive to hydrate saturation with unexpected peaks observed between 3 and 5 per cent hydrate saturation. It is thought that viscous squirt flow of absorbed water or free gas within the pore space is enhanced by hydrate cement at grain contacts and by the nanoporosity of the hydrate itself. These results show for the first time the dramatic effect methane gas hydrate can have on seismic wave attenuation in sand, and provide insight into wave propagation mechanisms. These results will aid the interpretation of elastic wave attenuation data obtained using marine seismic prospecting methods. © 2005 The Authors Journal compilation © 2005 RAS.
Keywords: GAS HYDRATES; LABORATORY RESONANT COLUMN; SAND; SEISMIC ATTENUATION